Revitalisasi Kinerja Guru PAI Dalam Bidang Ekstrakurikuler Di Era Globalisasi - Makhmudah, Siti (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2015)
The teaching profession is still much discussed and questioned the whole circle. Seeing the reality demands of modern times, that in an increasingly complex world of education requires improvement in the arrangement and to organize the necessary personal intelegent capable and responsive. Teacher performance is always in the spotlight because of the challenges facing increasingly complex. With the background of this problem, researchers interested in assessing and dig deeper into how the figure of a teacher, especially PAI teacher performance. The teaching profession is still much discussed and questioned the whole circle. Due to the problems experienced by the Islamic religious education teachers or educational institutions today increasingly converging. The problems that are studied include: a) the process of teaching and learning in class b) Extracurricular activities c) Creation of a religious atmosphere in the school environment. The problem is interesting to study the researcher perspective, as any good instituted in school/madrasah. A teacher in the eyes of the public in the code of ethics of teachers, or in view of religion is a complicated problem that is not discussed much less exhausted in this globalization era.